KEPEMIMPINAN DALAM PEMBANGUNAN SEKTOR PUBLIK BERBASIS PENGETAHUAN - Ida Farida (Universitas Bandar Lampung (UBL), 2016)
Various challenges in the era of globalization, decentralization, and knowledge-based economy, and the advancement of information technology in the 21st century requires government institutions in the developed as well as developing countries to develop models of new public sector leadership. In this case, the issues of globalization, decentralization, and advances in information technology should be a major concern for government institutions in this century. Globalization of economic and social policies have led to the importance of having new capacity in response to a variety of opportunities related to the implications of international policy issues and interests of national development. One of the essential components of these issues is leadership in knowledge based public sector.